A simple SPE-UPLC-MS/MS method for determination of 9 antibiotics in surface water - Hoai, Pham Thi Thu; Binh, Chu Dinh; Tu, Vu Cam; Thao, Nguyen Thi; Mai, Duong Thi Quynh; Thu, Nguyen Thi; Ta, Thi Thao; Vu, Van Tu; Hue, Nguyen Thi; Hoi, Bui Van (Vietnam Journal of Science and Technology, 2022)
The overuse of antibiotics is losing its effectiveness due to increased antibiotic resistance in bacteria. Over the last two decades, the evaluation of antibiotic residues in the environment has greatly attracted the attention of researchers around the world. The more new groups of antibiotics were validated to use in medical treatment, the more antibiotic residues were discharged into the environment. In this work, a combined SPE-UPLC-MS/MS method was developed and validated for simultaneously analyzing 9 antibiotic compounds belonging 3 different groups which are tetracyclines (tetracycline – TET, chlortetracycline – CHL, oxytetracycline – OXY), fluoroquinolones (ciprofloxacin – CIP, norfloxacin – NOR, ofloxacin – OFL) and macrolides (azithromycin – AZI, erythromycin – ERY, clarithromycin – CLA) in surface water. All target analytes were separated on a reversed-phase column (Water BEH C18 column, 1.7 µm particle size, 100 x 2.1 mm) coupled with a mass in tandem employing positive electrospray ionization (+ESI). All target analytes were well separated with an overall run time of 16 minutes. The limit of detection was from 0.2 to 10 µg L-1. The extraction process has been successfully optimized using the HLB column (Oasis, 6mL, 200mg, Waters) with recoveries from 71 to 125%. The optimized method was finally applied to analyze ten surface water samples (lake and river). OFL, CLA, and ERY were most found in lake samples at concentrations from 35 – 570.3 ng.L-1 while only CIP was found in all river samples. The other compounds were also detected in both types of samples but the concentrations were lower than the quantification limit.